Predictive factors of occupational stress among nurses during the COVID-19 pandemic: a cross-sectional study in Kashan, Iran - Zahra Ghaderi; Zahra Tagharrobi; Zahra Sooki; Khadijeh Sharifi (BMC, 2024)
Abstract Background Considering the severe and sudden changes in the job conditions of nurses during the covid-19 pandemic, the increase in job tensions during this critical period and its consequences on the quantity and quality of nursing care, this study aims to investigate the job stress of nurses during the covid-19 pandemic and its predictors in Iran. Methods This cross-sectional study was conducted on 400 nurses in 'Kashan', Iran, who were randomly selected using stratified sampling. Data were collected using two questionnaires on occupational stress and potential related factors. The data were analyzed in SPSS version 16. Results The results showed that the occupational stress of nurses in Iran was at a medium to high level with a mean and standard deviation of 103.773 ± 15.742 (scale of 34-136). Factors such as satisfaction with physical health, quality of work life, satisfaction with the availability of facilities, sense of coherence, education level, work experience, job burnout, male gender, being native, and workplace were predictors of occupational stress and explained 23.3% of the variance in occupational stress score. The highest contribution was related to satisfaction with physical health. Conclusion Considering the consequences of occupational stress for nurses, it is crucial for health and nursing authorities to take these factors into consideration in policy-making and planning.